Systematic Review: Impact of Air Pollution on DNA Methylation - Akbar, Muhammad Ihzario Ibrahim; Tualeka, Abdul Rohim; Zurimi, Suardi; Jalaludin, Juliana (Universitas Airlangga, 2025)
Background: Quality of life is an important. It is influenced by exposure to chemicals in the body, such as air pollution, which can damage supporting life in the future. Objective: The aim of writing this systematic review is to specify the impact of air pollution on DNA methylation. Methods: The method in this study uses the Preferred Reporting Items for Systematic Review and Meta-analyses, this methode is carried out by searching for data in the form of articles or journals, which is carried out using the keywords